PENERAPAN PEMBELAJARAN OUTDOOR LEARNING DALAM MENINGKATKAN MINAT BELAJAR IPAS DI SDN PEDURUNGAN KIDUL 02 - Pangestu, Putra Aji; Patonah, Siti; Suyitno, Andy; Ayu Nyoman, Ngurah (LPPM STAI Muhammadiyah Probolinggo, 2024)
Education is carried out so that learning objectives can be achieved. Educational goals will be achieved through the learning process. In the learning process teachers must have learning methods in each subject. One of the important subjects in elementary school is Natural and Social Sciences (IPAS), which discusses how living things interact with each other and understand phenomena that occur in their environment, therefore science subjects are often considered difficult. So this results in students' interest in studying science at school being low. A learning method that can increase student interest is using outdoor learning or learning outside the classroom. The aim of this research is to describe and analyze the application of out-of-class learning methods in increasing interest in learning science and science for VA class students at SDN Pedurungan Kidul 02, Semarang City with a sample of 29 students. The research method used is Classroom Action Research, consisting of 2 cycles and 4 main activities, namely planning, action, observation and reflection. Based on the results of data analysis and discussion, it can be seen that the application of learning outside the classroom can increase students' interest in learning science and science. The results of research on pre-action outdoor learning obtained a percentage of only 40%. Meanwhile, after outdoor learning was implemented, students' interest in learning science and science showed a percentage increase of 89%. It can be concluded that the application of learning outside the classroom can increase students' interest in learning science and technology.